2016
DOI: 10.1051/limn/2016016
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, distribution and habitat requirements of aquatic insect communities in tropical mountain streams (South-eastern Guinea, West Africa)

Abstract: Considering that knowledge of the biodiversity of a region is the first step toward its conservation and given the paucity of studies on aquatic insects from the Simandou streams, the diversity of these communities was assessed. Aquatic insects were sampled with a hand-net (mesh size: 250 mm) on four occasions between March 2011 and September 2012 at 27 sites. Environmental variables were also recorded. Overall, 129 taxa belonging to 51 families and eight orders were recorded. Multivariate analyses gathered si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
(46 reference statements)
0
5
0
1
Order By: Relevance
“…Aquatic macroinvertebrates structure was described through taxonomic composition, rarefied richness, Shannon-Weiner index, Pielou's Evenness index, frequency of occurrence and Trichoptera, Plecoptera and Ephemeroptera index (EPT). Taxa richness was rarefied to eliminate any bias related to differences in abundances between samples (Heck et al, 1975;Edia et al, 2016). Calculations were performed using the lowest abundance (11 individuals for this study) found in all stations as the target number of individuals (Oksanen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic macroinvertebrates structure was described through taxonomic composition, rarefied richness, Shannon-Weiner index, Pielou's Evenness index, frequency of occurrence and Trichoptera, Plecoptera and Ephemeroptera index (EPT). Taxa richness was rarefied to eliminate any bias related to differences in abundances between samples (Heck et al, 1975;Edia et al, 2016). Calculations were performed using the lowest abundance (11 individuals for this study) found in all stations as the target number of individuals (Oksanen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a higher proportion of freshwater species are threatened with extinction than their terrestrial counterparts (Dudgeon 2010). Therefore, deterioration of aquatic biodiversity has become one of the main concerns in recent conservational and ecological studies in various parts of the world (Che Braun et al 2014;Edia et al 2016;Hill et al 2016;Principe et al 2019).…”
Section: Implication Of the Study For Conservationmentioning
confidence: 99%
“…Furthermore, headwater streams offer vital services to humankind, namely the storage, regulation, and purification of water (Bucker et al 2010). All these services depend on healthy ecosystems that are currently endangered by degradation (Edia et al 2016). Although, headwater streams may be small in size, they provide habitats for a rich array of species, which enhances the biological diversity of the entire river system (Meyer et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La richesse en taxons a été raréfiée pour éviter tout biais lié aux différences d'abondance entre les échantillons (Paillex et al, 2007 ;Edia et al, 2016). Dans la présente étude, la raréfaction a été appliquée à la richesse taxonomique par échantillon en utilisant la plus faible abondance (237 individus) enregistrée dans les échantillons comme nombre cible d'individus (Okasanen et al, 2013 L'indice de similarité de Jaccard, (1908) a été utilisé pour comparer les sites deux à deux, car il évalue la ressemblance entre deux relevés en faisant le rapport entre les espèces communes aux deux relevés et celles propres à chaque relevé.…”
Section: Matériel Et Méthodes Milieu D'étudeunclassified